Integrasi Teori Konstruktivisme dalam Desain Multimedia Pembelajaran - Hukom, Julham (CV. SINAR HOWUHOWU, 2025)
The integration of constructivist theory into multimedia learning design is a crucial approach to improving the quality of learning processes in higher education. This literature review article analyzes the principles of multimedia learning, their relevance to constructivist theory, design integration models, impacts on student learning outcomes, and implementation challenges. The study was conducted through a systematic review of academic literature published between 2000 and 2024, with an emphasis on publications in the last five years. The results indicate that multimedia design principles such as dual-channel, contiguity, coherence, and guided discovery are strongly relevant to constructivism, which emphasizes active engagement, exploration, and knowledge construction. Integrating the two principles results in multimedia designs that support conceptual understanding, problem-solving, learning motivation, and higher-order thinking skills. However, successful implementation is strongly influenced by the lecturer's pedagogical readiness, technological skills, content suitability, and potential cognitive load constraints. These findings underscore the importance of a focused and theory-based design approach to producing effective and meaningful multimedia learning. This article also offers directions for further research related to artificial intelligence-based adaptive multimedia, digital collaborative design, and long-term evaluation of the effectiveness of constructivist multimedia.